Status and Requirement of Boron for Tropical Tuber Crops Under Laterite (Typic Kandi Ustult) Soils - K., Susan John; D., Karthika; T., Sruthi; J., Sreekumar; K., Sunil Kumar; P. S., Anju (JOURNAL OF ROOT CROPS, 2020)
Tropical tuber crops also require the micronutrient B for its growth and productivity as in the case of all other crops. The very low B content in the major tropical tuber crops growing soils of Kerala could cause the manifestation of B deficiency symptoms both in vegetative parts and tubers in the case of cassava and sweet potato. The recent occurrence of symptoms akin to hollow/brown heart of potato, in yams (Dioscorea), necessitated to take up experiments related to B nutrition to understand the etiology of this problem. Since the manifestation was noticed in a typical laterite soil (Typic Kandi Ustult) of the farm of ICAR-CTCRI and under similar soils of the State, a rapid nutrient status appraisal was made for the five blocks of CTCRI farm for nutrients viz., available B and exchangeable Ca as there exists a synergism between these two nutrients. A sorption study too was conducted to predict the rate of application of B for soils of varying B status. A total of 95 soil samples collected from these blocks taking into account the terrain and present cropping/fallow were analysed. Wide variation was seen in the available B status ranging from 0.14-0.419 ppm for block I and II, 0.172-0.419, 0.172- 0.848, 0.150-1.052 ppm for block III, IV and V respectively with mean values as 0.317, 0.242, 0.289, 0.331 and 0.356 ppm respectively. The mean exchangeable Ca content of the soils of these blocks were 0.896, 1.015, 0.640, 0.989, 0.877 meq 100 g-1 soil with ranges as 0.565-1.303, 0.741-1.387, 0.534-0.866, 0.762-1.215 and 0.591-1.254 meq 100 g-1 soil respectively. To understand the interaction between these nutrients, the correlation worked out indicated synergism or significant positive correlation (r=0.537) only in block V. Sorption study could find a linear increase in the quantity of B extracted in the soils of varying B contents ranging from 0.1-1.0 ppm under addition of incremental rates of B from 0.25 to 4.0 ppm. The inverse prediction function method employed to predict the quantity of B to be applied to attain soil B status to either the soil critical level of B (0.5 ppm), double (1.0 ppm) and thrice (1.5 ppm) the critical levels in soils of the above B status (0.1-1.0 ppm) was found as 0.78-3.09, 1.80-7.21 and 7.4-11.33 ppm respectively. Though the low soil available B and exchangeable Ca content can be attributed as one of the reasons for the problem manifested in yams, detailed studies are needed to explore the role of abiotic factors especially moisture and heat stress in the dynamics of these nutrients at different growth stages of the crop.